The Efficacy of Acupuncture on Tic Disorders in Children: A Retrospective and Propensity Score-Matched Study - You, Hai-Zhen; Zhou, Yi-Fang; Yu, Ping-Bo; Xie, Jing; Chen, Jia; Li, Ji-Jun; Wang, Guang-Hai; Sun, Ke-Xing (Frontiers in Pediatrics, 2021)
Background: At present, the efficacy rate of the conventional treatment for tic disorders is approximately 30–60%. This study retrospectively analyzed the efficacy of acupuncture treatment combined with conventional treatment for tic disorders over the course of 12 weeks and evaluated the effectiveness of acupuncture treatment in these patients. Methods: Data were collected from the Shanghai Children’s Medical Center between June 2020 and March 2021. A total of 250 patients with tic disorders were included in the study. A total of 122 patients were included in the combined acupuncture therapy and conventional treatment group and 128 patients were included in the conventional treatment only group. Propensity score matching analyses were used to compensate for differences in baseline characteristics, and each group included 78 matched patients. Reductions in the Yale Global Tic Severity Scale score were observed in the two groups after 12 weeks of treatment. Results: The eight covariates, including the Yale Global Tic Severity Scale score at the patient’s first visit, age, gender, information on heredity, household registration, parental education level, family structure, and body mass index in the two groups, reached equilibrium after the match (P > 0.05). Relative to changes in the conventional treatment group, the reduction in the total Yale Global Tic Severity Scale score after 12 weeks of treatment was greater for the acupuncture therapy combined with conventional treatment group (odds ratio = 2.94, 95% confidence interval: 1.03, 8.39, P = 0.04), and this association was stronger for patients who had significant vocal tics (β coefficient = 0.29, 95% confidence interval: 0.88, 2.68, P = 0.001). The clinical efficacy observed in the observation group was statistically significantly better than that of the control group. Conclusions: We found that the therapeutic effect of a combination of acupuncture treatment and conventional treatment for tic disorders is superior to that of conventional treatment alone. Hence, our results indicate that acupuncture could be a first-line adjuvant treatment for tic disorders characterized by vocal tics.